Postpartum Contraceptive Use and Its Determinants in Ethiopia: A Systematic Review and Meta-analysis - Tsegaye Mehare; Birhanie Mekuriaw; Zelalem Belayneh; Yewbmirt Sharew (Hindawi Limited, 2020)
Background. Postpartum contraceptive use is defined as the avoidance of short spaced pregnancies and unintended pregnancy through the first 12 months after delivery. In Ethiopia, different studies have been conducted to assess the prevalence of postpartum contraceptive use and associated factors. The findings of these studies were inconsistent and characterized by great variability. Therefore, the aim of this systematic review and meta-analysis was to estimate the pooled prevalence of postpartum contraceptive use and determinants in Ethiopia using the accessible studies. Methods. The articles were identified through electronic search of reputable databases (MEDLINE through PubMed, EMBASE, HINARI, Science Direct, and Cochrane Library) and the hand search of reference listed in previous prevalence studies to retrieve more. 18 articles are included based on a comprehensive list of inclusion and exclusion criteria. Two authors independently extracted all necessary data using a standardized data extraction format. STATA 14 statistical software was used to analyze the data. The Cochrane Q and I2 test were used to assess the heterogeneity between the studies. A random effects model was calculated to estimate the pooled prevalence of postpartum contraceptive use. Moreover, the determinants for family planning use were reviewed. Results. The pooled prevalence of family planning use among mothers during the postpartum period in Ethiopia was 48.11% (95% CI: 36.96, 59.27). Besides, subgroup analysis revealed that the highest family planning use prevalence among postpartum mothers was observed in Addis Ababa, 65.41 (95% CI: 48.71, 82.11). Resumed sexual activity: 7.91 (95% CI: 4.62, 13.55), antenatal care: 4.98 (95% CI: 2.34, 10.21), secondary school and above level of maternal education: 3.53 (95% CI: 1.67, 7.45), postnatal care: 3.16 (95% CI: 1.7, 5.88), menses resumption: 3.12 (95% CI: 1.52, 6.39), and ≥6 months of postpartum period: 2.78 (95% CI: 1.97, 3.93) have shown a positive association with the use of family planning among mothers in the postpartum epoch. Conclusions. In this study, family planning use among mothers of the postpartum period in Ethiopia was significantly low compared to the existing global commendation on postpartum contraceptive use. Resumed sexual activity, antenatal care, secondary and above level of maternal education, postnatal care, menses resumption, and postpartum period≥6 months were found to be significantly associated with postpartum contraceptive use.